SUPER CONTRA HARMONIC MEAN LABELING OF GRAPHS - Ezhilarasan . M, Karunakaran .V ,K . Balasangu, Malathi . T (South Eastern European Journal of Public Health, 2025)
The concept of Contra Harmonic mean labeling was introduced by S. Somasundaram and R. Ponraj [6 ] . Further, the concept of Super mean labeling was introduced by R. Ponrajand D.Ramya [7]. In this paper we investigate the Super Contra harmonic mean labeling for some subdivision of path , sunlet ,bistar related graphs.